Implementasi Anggaran Pada Usaha Mikro Dan Kecil Di Surabaya - Setiadi Alim Lim; Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
One of the factors are identified as the cause of failure of micro, small and medium enterprises is the absence of a good financial plan in the form of budget. In this research will be studied about budget implementation in business activity from micro and small entrepreneurs engaged in food/beverage business in Kampung Roti, Surabaya, East Java. The results showed 42,11% of micro and small entrepreneurs have used the budget and 57,89% have not used the budget. Small and micro entrepreneurs who already use the budget as much as 42,11% argue that the useful budget helps their business activities. The most widely used type of budget is the material purchase budget, cash budget and cost budget. Micro and small entrepreneurs argue that the purposes of budgeting are for planning, decision-making and controlling operations (42,11%), monitor business and measure business performance (31,58%) and to motivate (26,31%). Small and micro entrepreneurs also believe that budget implementation constraints are resource limitations power required (92,11%), lack of understanding of budgeting (86,84%), lack of management/owner support (57,89%) and only prepared when there is more time (42,11%).